Congenital Dislocation of the Hip (Res Medica, 2013)
Based on a Dissertation read before the Society on January 19th. 1962.The subject of Congenital Dislocation of the hip (C.D.H.) is so vast and complicated that anyone who attempts to correlate the known facts and numerous hypotheses into a neat, compact monograph, is doomed to failure before he starts. One of the main difficulties is the almost universal disagreement about the various aspects of the disease, whether of aetiology, pathology, diagnosis or treatment. In these pages, I shall confine myself to discussing some of the active steps one can take in the prevention and cure of the condition.